Implementasi Resiko Kepatuhan Pada Karyawan Dinas Perdagangan Sumatera Selatan - Oki Sapitri Menghayati; Siti Ambarwati; Mitra Anggrainy; Thia Fathona; Ana Mariya; Sirat Nispuana; M Farhan Wijaya (FEB Universitas Maritim Semarang, 2024)
This research discusses the implementation of compliance for trade service employees which is being re-implemented for the community in connection with the rise of street vendors in the South Sumatra province. The research method used in this research is a qualitative research method. Qualitative research methods are research methods that prioritize social phenomena and provide evidence that is socially coherent and specific in relation to the cases or phenomena that occur. The problems studied in qualitative research are relatively clearer and easier to understand because case studies prioritize real events that occur in the community. The research results show that the implementation of the level of compliance among trade service employees is still relatively lacking. This is because the trade department is still not specific and active enough to remind the public regarding the trading process within the South Sumatra provincial department which still trades anywhere. The follow-up carried out by the trade service is still relatively in the form of a warning. Apart from that, employees in the area or environment of the South Sumatra provincial trade office are still lacking in implementation regarding the prohibition on carrying out trading actions that can damage public facilities, trade on the street, fill sidewalks and also eliminate the comfort of other people regarding pedestrians.